Function evaluation of the autoanalyser internal quality control of the Kehua Polaris c2000 automatic biochemical analyser: Evaluation of the Kehua Polaris c2000 autoanalyser quality control system - Wang, Yiyi; Shi, Lei; Zhang, Jue; Chen, Chen (Journal of Medical Biochemistry, 2024)
Objective: The present study aims to (1) evaluate the autoanalyser quality control (QC) module of the Kehua Polaris c2000 automatic modularised biochemical analyser and (2) verify the impact of the analyser’s automatic implementation of internal QC (IQC) testing at a set time point on the results of IQC and turnaround time (TAT). Methods: For 5 consecutive days, three different methods were used to conduct IQC. Method 1: Internal QC was carried out at 8:00 every day. Method 2: The QC products were placed in the instrument calibration QC plate in the afternoon, and the instrument was set to automatically measure the products at 7:00 the next day. Method 3: The QC products were placed in the instrument calibration QC plate, and the instrument was set up for automatic measurement at 7:30 every day. All three methods were compared and evaluated. The effect of IQC on the TAT was monitored using method 2. Results: There were no statistical differences in the IQC results between methods 2 and 1. However, there were statistical differences in some items between the results of methods 3 and 1; thus, the IQC results of method 2 can be adopted. The implementation of method 2 for IQC can help achieve a significant TAT-saving of 35.23 min during the automatic retest process after the IQC indicates an out-of-control situation. This time reduction is highly valuable for improving efficiency and streamlining the testing workflow. Conclusion: Using the autoanalyser QC module of the Kehua Polaris c2000 automatic modular biochemical analysis system to perform IQC has no impact on the IQC test results and can save TAT, as well as automatically correct most out-of-control occurrences.